2014
DOI: 10.18632/oncotarget.1953
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA profiling of novel African American and Caucasian Prostate Cancer cell lines reveals a reciprocal regulatory relationship ofmiR-152and DNA methyltranferase 1

Abstract: miRNA expression in African American compared to Caucasian PCa patients has not been widely explored. Herein, we probed the miRNA expression profile of novel AA and CA derived prostate cancer cell lines. We found a unique miRNA signature associated with AA cell lines, independent of tumor status. Evaluation of the most differentially expressed miRNAs showed that miR-132, miR-367b, miR-410, and miR-152 were decreased in more aggressive cells, and this was reversed after treatment of the cells with 5-aza-2′-deox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 39 publications
6
58
5
Order By: Relevance
“…Braconi et al (14) first described that the DNA methyltransferase 1 (DNMT1) gene is a direct target of miR-148a and miR-152 by using luciferase reporter constructs, which revealed that miR-152 could target the 3'-UTR of DNMT1, resulting in a significant reduction of DNMT1 at both mRNA and protein levels. This finding was further confirmed in subsequent studies on ovarian cancer (15), endometrial cancer (9), nickel sulphide (NiS)-induced cell malignant transformation (16), breast cancer (17), hepatitis B virus-related hepatocellular carcinoma (18), pancreatic cancer (19) and prostate cancer (20). In addition, E2F transcription factor 3, mesenchymal to epithelial transition (MET), rapamycin-insensitive companion of mechanistic target of rapamycin (9), insulin-like growth factor 1 receptor (IGF-1R), insulin receptor substrate 1 (IRS1) (17), a disintegrin and metalloproteinase metallopeptidase domain 17 (ADAM17) (21,22), Kruppel-like factor 4 (KLF4) (23), fibroblast growth factor 2 (FGF2) (24), winglessrelated integration site (Wnt1) (25), cluster of differentiation (CD) 151 (26), matrix metalloproteinase 3 (MMP3) (27) and transforming growth factor alpha (28) have been identified as targets of miR-152 in a wide array of human malignancies.…”
Section: Experimentally Validated Targets Of Mir-152 In Human Cancermentioning
confidence: 56%
See 3 more Smart Citations
“…Braconi et al (14) first described that the DNA methyltransferase 1 (DNMT1) gene is a direct target of miR-148a and miR-152 by using luciferase reporter constructs, which revealed that miR-152 could target the 3'-UTR of DNMT1, resulting in a significant reduction of DNMT1 at both mRNA and protein levels. This finding was further confirmed in subsequent studies on ovarian cancer (15), endometrial cancer (9), nickel sulphide (NiS)-induced cell malignant transformation (16), breast cancer (17), hepatitis B virus-related hepatocellular carcinoma (18), pancreatic cancer (19) and prostate cancer (20). In addition, E2F transcription factor 3, mesenchymal to epithelial transition (MET), rapamycin-insensitive companion of mechanistic target of rapamycin (9), insulin-like growth factor 1 receptor (IGF-1R), insulin receptor substrate 1 (IRS1) (17), a disintegrin and metalloproteinase metallopeptidase domain 17 (ADAM17) (21,22), Kruppel-like factor 4 (KLF4) (23), fibroblast growth factor 2 (FGF2) (24), winglessrelated integration site (Wnt1) (25), cluster of differentiation (CD) 151 (26), matrix metalloproteinase 3 (MMP3) (27) and transforming growth factor alpha (28) have been identified as targets of miR-152 in a wide array of human malignancies.…”
Section: Experimentally Validated Targets Of Mir-152 In Human Cancermentioning
confidence: 56%
“…These results suggest that the hypermethylation of the CpG island of miR-152 may downregulate its expression, and may be involved in endometrial cancer. Due to the hypermethylation of its CpG island, silencing of miR-152 expression and overexpression of DNMT1 were also observed in NiS-transformed cells (16), breast cancer (17) and prostate cancer (20). Notably, there may be a crucial functional crosstalk between miR-152 and DNMT1 via a double-negative feedback regulatory loop, as speculated by Ji et al (16) regarding the classic 'chicken and egg' argument.…”
Section: Mir-152 As a Tumor Suppressor Mirna In Cancermentioning
confidence: 93%
See 2 more Smart Citations
“…miR-1b-1, miR-26a, miR-30c-1, miR-219 and miR-301 were shown to be differentially-expressed in prostate tumors of AA and EA racial backgrounds (37). Later, Theodore et al examined the expression of miR-26a in prostate cancer cell lines of AA (RC77N/E, RC77T/E and MDA-2PCa-2b) and EA (PrEC, RC-92a and PC-3) origin, representing non-malignant, malignant, and metastatic prostate cancer tumors, respectively (38,39). They observed increased (2.2. to 13.3. folds) expression of miR-26a in AA prostate cancer cells of all three stages and grades, when compared with EA cell lines of similar clinical stage and pathological-grade.…”
Section: Molecular Bases Of Prostate Cancer Racial Disparitiesmentioning
confidence: 99%